Biocompatible Nanomaterials as an Emerging Technology in Reproductive Health; a Focus on the Male - Fraser, Barbara; Peters, Alexandra E.; Sutherland, Jessie M.; Liang, Mingtao; Rebourcet, Diane; Nixon, Brett; Aitken, Robert J. (Frontiers in Physiology, 2021)
A growing body of research has confirmed that nanoparticle (NP) systems can enhance delivery of therapeutic and imaging agents as well as prevent potentially damaging systemic exposure to these agents by modifying the kinetics of their release. With a wide choice of NP materials possessing different properties and surface modification options with unique targeting agents, bespoke nanosystems have been developed for applications varying from cancer therapeutics and genetic modification to cell imaging. Although there remain many challenges for the clinical application of nanoparticles, some of these may be overcome with the recent development of hybrids comprising polymeric and exosomal nanoparticles. Indeed, these hybrid NPs may resolve problems associated with the uptake and clearance of NPs by the mononuclear phagocyte system (MPS), thus increasing their in vivo stability and therapeutic efficacy. In recognition of this potential, this review seeks to present recent NP research with a focus on the exciting possibilities posed by their application within the fields of male reproductive medicine, health, and research.